2014
DOI: 10.1111/1471-0528.12580
|View full text |Cite
|
Sign up to set email alerts
|

Management and outcomes for elderly women with vulvar cancer over time

Abstract: Methods Women were stratified by age: <50, 50-64, 65-79, and ≥80 years. Differences in survival and treatment patterns were analysed between age groups. Multivariate logistic regression models were constructed to examine treatment patterns. KaplanMeier and Cox proportional hazards survival methods were used to assess survival.Main outcome measures Vital status from the date of diagnosis until death, censoring or last follow-up. ResultsThe final study group consisted of 8553 women, 1806 (21.12%) <50 years, 2141… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Severe pain affects daily activities such as walking, sitting, urinating and sleeping . Age, comorbidity, natural history, and previous treatment of cancer limit the feasibility of therapies such as chemotherapy and radiotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Severe pain affects daily activities such as walking, sitting, urinating and sleeping . Age, comorbidity, natural history, and previous treatment of cancer limit the feasibility of therapies such as chemotherapy and radiotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 65% of VSCCs are HPV-positive and the oncogenic high-risk types HPV-16/-18/-31/-33 are most frequently detected [ 6 ]. However, the burden of VSCC still lies with older women, in whom survival rates are low due to more aggressive tumors, diagnosis at later stages and frequent under-treatment [ 7 , 8 ]. Surgery - consisting of local tumor excision with sentinel or inguinofemoral lymph node dissection - is considered the cornerstone of therapy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Squamous cell carcinoma is the most prevalent subtype. 1,2 Traditionally, curative treatment of squamous cell VC includes radical vulvectomy plus (superficial and deep) inguinal-femoral lymphadenectomy. 3 However, growing evidence suggested that less invasive procedures (ie, simple vulvectomy, wide local excision, sentinel node biopsy) provide similar long-term results, minimizing morbidity.…”
mentioning
confidence: 99%